PS-BPC11-1: ASSOCIATION BETWEEN INCREASED ABDOMINAL CIRCUMFERENCE AND FUTURE DEVELOPMENT OF HYPERTENSION IN MILDLY OBESE MIDDLE-AGED INDIVIDUALS. (January 2023) - Ninomiya, Yuichi; Kawasoe, Shin; Kubozono, Takuro; Tokushige, Akihiro; Ichiki, Hitoshi; Ikeda, Yoshiyuki; Miyahara, Hironori; Tokushige, Koichi; Ohishi, Mitsuru
Abstract : Objective: While increased abdominal circumference is reportedly associated with an increased risk of hypertension, few studies have examined sex-specific differences in this relationship. Here, we investigated sex-specific differences in the association between increased abdominal circumference and future development of hypertension. Design and method: Among 53, 281 middle-aged (40 to 59 years old) individuals who underwent a health examination at least once between 2007 and 2014, we examined 890 of 1, 744 individuals with mild abdominal obesity (above the median waist circumference) because examination data at 3- and 8-year follow-ups for these individuals were available. Propensity score (PS) matching, based on the first examination data, was used to match participants with an increased waist circumference (IWC; ≧ 3 cm at the 3-year time point, IW group) with those not meeting this criterion (non-IW group). Variables, such as age, body mass index, smoking status, alcohol consumption, estimated glomerular filtration rate, systolic blood pressure (SBP), diastolic blood pressure (DBP), and hypertension (defined as SBP ≧ 140 mmHg and/or DBP ≧ 90 mmHg), were used for PS matching. Blood pressure and hypertension incidence were compared between two groups at the 8-year time point. Results: PS matching resulted in 91 men and 85 women in each group. In men, SBP and hypertension incidence at the 8-year time point were significantly higher in the IW than in the non-IW group (SBP: 126.2 ± 12.8 vs. 121.7 ± 14.8 mmHg, P < 0.05; hypertension incidence: 44.0% vs. 27.5%, P < 0.05). In women, there were no significant differences in these two parameters between the two groups (SBP: 123.3 ± 15.8 vs. 120.2 ± 16.8 mmHg, P = 0.22; hypertension incidence: 24.7% vs. 29.4%, P = 0.49). Conclusions: A sex-specific association between increased abdominal circumference and future development of hypertension was observed in mildly obese middle-aged men, but not women.